Faculty Perceptions on Use of the Clinical Reasoning Assessment Tool to Support Learning in Physical Therapist Students: A Qualitative Study. Issue 1 (2nd March 2022) - McDevitt, Amy; Rapport, Mary Jane; Rodriguez, Jenny; Miller, Matthew
Abstract : Supplemental Digital Content is Available in the Text. Abstract : Introduction: The clinical reasoning assessment tool (CRAT) is a patient-centered tool that was developed to assess students' progress in the development of clinical reasoning. The purpose of this qualitative study was to explore how academic and clinical faculty in a physical therapist curriculum use the CRAT to support the development and assessment of clinical reasoning in physical therapist student learners. Review of Literature: Clinical reasoning is a multifaceted process crucial to optimal patient care. The ability to teach, learn, and assess the development of clinical reasoning skills continues to be challenging due to the complexity of this necessary skill. Methods: A qualitative, thematic analysis approach was used to achieve the study objective. Qualitative data were collected from 3 focus group sessions, transcribed, and analyzed to identify, summarize, and interpret entry-level physical therapist educators' perceptions and experiences using the CRAT with physical therapist students. Results: Physical therapist educator participants ( N = 13) reported using the CRAT as a guide for learning and assessment. Three qualitative themes were identified: 1) fostering understanding of clinical reasoning through organization and structure; 2) facilitating clinical reasoning through dialogue and self-reflection; and 3) assessment of clinical reasoning in the learner through benchmarking. Discussion and Conclusion: Study findings suggest that the structure and organization of the CRAT facilitated dialogue, student self-reflection, and assessment of clinical reasoning through benchmarking. The CRAT may support faculty in their work to further the learners' acquisition of clinical reasoning skills.